Principal and Vice Principal's Perception of Curriculum Affairs Towards The Performance of Physical Educators at State Senior High School Level In Banda Aceh City - Boihaqi, Boihaqi -; Akbar, Aldiansyah (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. Teachers play a crucial role as the spearhead of education, not only by imparting knowledge but also by facilitating learning and nurturing students' fundamental potential and abilities to their fullest. Various factors influence teacher performance, including internal factors such as competence and work motivation. Generally, the quality of education serves as a key benchmark for evaluating teachers' performance. This study aims to assess the perceptions of principals and vice principals of curriculum regarding the performance of physical education teachers at the State Senior High School (SMA Negeri) level across Banda Aceh City. Material and Method. The study involved 26 participants, consisting of principals and vice principals of the curriculum section from various SMA Negeri in the city. Data collection was conducted through direct field visits to schools, utilizing both questionnaires and interviews. Result. The findings of this study reveal several key insights. The results indicate that 85% of principals and vice principals generally perceive physical education teachers in SMA Negeri throughout Banda Aceh City as performing well in the teaching and learning process. Additionally, 76% of them reported that most teachers prepare lesson plans aligned with the school curriculum, while 77% of physical education teachers effectively teach the subject comprehensively. Furthermore, 85% of principals stated that physical education teachers demonstrate good discipline at school. Conclusion. The study concludes that physical education teachers in State Senior High Schools across Banda Aceh City generally demonstrate good performance in teaching, lesson planning, and discipline, as perceived by principals and vice principals.